(untitled) (Numerus academy review, 2026)
The work of the woman and her participation to the economic development constitute an important subject due to her position in the society as she is the half of the society. This is why, the work of the woman remains one of the most discussed subjects between experts and professionals especially the night work of the woman because it breaks the general rule which provides that the work should be performed during the day so that all legislations works to limit the freedom of bosses in this kind of grade to avoid exploitation of workers especially women. The importance of this study is in the nature of the problem that it studies so that it shows the legitimacy of the night work thing that allows us taking into account the provisions on international agreements thereto in one hand and the provisions instituted by the Algerian legislator in order to protect the woman in the other hand.